(untitled) (Clinics, 2012)
OBJECTIVE: The standard therapy for patients with high-level spinal cord injury is long-term mechanical ventilation through a tracheostomy. However, in some cases, this approach results in death or disability. The aim of this study is to highlight the anesthetics and perioperative aspects of patients undergoing insertion of a diaphragmatic pacemaker. METHODS: Five patients with quadriplegia following high cervical traumatic spinal cord injury and ventilator-dependent chronic respiratory failure were implanted with a laparoscopic diaphragmatic pacemaker after preoperative assessments of their phrenic nerve function and diaphragm contractility through transcutaneous nerve stimulation. ClinicalTrials.gov: NCT01385384. RESULTS: The diaphragmatic pacemaker placement was successful in all of the patients. Two patients presented with capnothorax during the perioperative period, which resolved without consequences. After six months, three patients achieved continuous use of the diaphragm pacing system, and one patient could be removed from mechanical ventilation for more than 4 hours per day. CONCLUSIONS: The implantation of a diaphragmatic phrenic system is a new and safe technique with potential to improve the quality of life of patients who are dependent on mechanical ventilation because of spinal cord injuries. Appropriate indication and adequate perioperative care are fundamental to achieving better results.